2021
DOI: 10.1177/23259671211035372
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Factors Affecting the Occurrence of Lateral Hinge Fracture After Medial Opening-Wedge High Tibial Osteotomy

Abstract: Background: Few clinical studies have reported the predictors of lateral hinge fracture (LHF) after medial opening-wedge high tibial osteotomy (MOWHTO). Purpose/Hypothesis: The purpose was to compare the incidence of LHF on plain radiographs versus computed tomography (CT) scans and to investigate the factors related to the development of LHF after MOWHTO. We hypothesized that (1) a higher LHF detection rate would be seen on CT scans versus plain radiographs and (2) LHF incidence would be related to opening ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Previous studies reported that a large opening gap was associated with LHF in medial opening wedge high tibial osteotomy (MOHTO). 8,10,14 Lee et al 14 reported that a large opening gap was a risk factor for LHF in MOHTO (OR, 1.615; 95% CI, 1.232-2.118; P = .001). Han et al 8 demonstrated that the osteotomy gap height was the only predictor of LHF (adjusted OR, 1.831; P = .016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that a large opening gap was associated with LHF in medial opening wedge high tibial osteotomy (MOHTO). 8,10,14 Lee et al 14 reported that a large opening gap was a risk factor for LHF in MOHTO (OR, 1.615; 95% CI, 1.232-2.118; P = .001). Han et al 8 demonstrated that the osteotomy gap height was the only predictor of LHF (adjusted OR, 1.831; P = .016).…”
Section: Discussionmentioning
confidence: 99%
“…9,26,27,29,33,36 Lateral hinge fracture (LHF) is a major cause of instability, loss of correction, malunion, and poorer outcomes. 22,33 Historically, the incidence of LHF has been reported to be as high as 30%. 25,37 In fact, a recent study by Lee et al 23 suggested that with advanced imaging, the incidence of LHF may be as high as 50% and that plain radiographs may underreport the incidence of LHF.…”
mentioning
confidence: 99%
“…However, this is not without controversy, as that was a single-surgeon series with large correction sizes 15,26 and other studies did not find such significant differences between imaging modalities. 12 HTO outcomes have improved with the advent of locking plates 19,35 and an appreciation for the ideal hinge position, 13,22,26 osteotomy level, 13,28,29 and extent of correction. 22,23,26 Recent studies have reported lower LHF rates of between 14% and 19%.…”
mentioning
confidence: 99%
See 2 more Smart Citations